Anterior Arthroscopic Approach for Multidirectional Shoulder Instability: Posterior Bone Block, Dynamic Anterior Stabilization, and Modified McLaughlin - Gonzalo de Cabo, M.D.; Pablo Ramos-Murillo, M.D.; David González-Martín, M.D., Ph.D.; Nuria Álvarez-Benito, M.D.; Francisco Poyato-Núñez, M.D.; Silvia Virginia Campesino-Nieto, M.D.; Manuel Leyes, M.D., Ph.D. (Arthroscopy Techniques)
Multidirectional shoulder instability represents an ongoing challenge for orthopaedic surgeons, and multiple techniques have been described to treat this condition. Posterior glenoid dysplasia is a known risk factor for posterior instability as well as persistent or recurrent instability following posterior stabilization procedures. Recurrent shoulder instability complicated by capsular insufficiency due to underlying soft tissue disorders or multiple prior failed surgical procedures poses a challenging surgical problem. A complex salvage surgery with multiple procedures is presented for patients with multidirectional instability or hyperlaxity, with an important posterior erosion component (mainly glenoid dysplasia) and loss of the anterior wall in previous surgical procedures to theoretically reduce recurrent dislocation rates. An anterior arthroscopic approach, including posterior bone block, dynamic anterior stabilization, and modified McLaughlin technique, is described in the present article.